Cardiovascular system functionality tests to individualize pre-season training process in elite weightlifting sport - Khomenko, R. V.; Antropova, E. V.; Tamozhnikova, G. V.; Faizrakhmanova, R. Kh. (Theory and Practice of Physical Culture, 2019)
Objective of the study was to offer cardiovascular system functionality tests to effectively individualize the pre-season training process in the modern elite weightlifting sport. Sampled for the study were Candi-date Masters and Masters of weightlifting sport split up into Reference (RG, n=15) and Experimental (EG, n=15) Groups; with the EG training system individualized to the cardiovascular system functionality test rates. Every option of the pre-season training system was strictly individualized by the process inten-sities, volumes, conditioning workloads and rehabilitation tools as required by the primary/ current/ ex-pected physical fitness and functionality rates. The cardiovascular system functionality tests included the HR and stroke volume rating tests. The pre-season training process individualization model driven by the cardiovascular system functionality tests was found beneficial for the elite weightlifters as verified by the EG progress in the cardiovascular system functionality, eased stress on the cardiac function regulation mechanisms in the sport-specific movement sequences and the improved adaptability rates in the EG ver-sus RG.